Organizational Bulk Email Systems: Their Role and Performance in Remote Work - Kang, Ruoyan; Zhu, Haiyi; Konstan, Joseph (2020)
ABSTRACT The COVID-19 pandemic has forced many employees to work from home. Organizational bulk emails now play a critical role to reach employees with central information in this work-from-home environment. However, we know from our own recent work that organizational bulk email has problems: recipients fail to retain the bulk messages they received from the organization; recipients and senders have different opinions on which bulk messages were important; and communicators lack technology support to better target and design messages. In this position paper, first we review the prior work on evaluating, designing, and prototyping organizational communication systems. Second we review our recent findings and some research techniques we found useful in studying organizational communication. Last we propose a research agenda to study organizational communications in remote work environment and suggest some key questions and potential study directions. Keywords bulk email, remote work, organizational communication ABOUT THE AUTHOR/S RUOYAN KONG University of Minnesota - Twin Cities kong0135@umn.edu I am Ruoyan Kong (www.ruoyankong.com). I am now a 2nd-year computer science phd student in Grouplens lab, U of Minnesota, working with Prof. Joseph Konstan. I’m interested in Human-computer Interaction, in the design of systems that use economic mechanisms and incentives to lead people to the behaviors that actually make things work. I’ve been working on the challenge of organization email – manage the balance between employee time, energy, and value of communication channels. HAIYI ZHU Carnegie Mellon University haiyiz@cs.cmu.edu I am the Daniel P. Siewiorek Assistant Professor of Human-Computer Interaction at Carnegie Mellon University. I received a B.S in Computer Science from Tsinghua University and an M.S. and a Ph.D. in Human-Computer Interaction from Carnegie Mellon University. I have received multiple NSF awards (CRII, Cyber Human System, EAGER on AI and Society, and Fairness in AI), several paper awards in venues such as CHI, CSCW, and Human Factors, and an Allen Newell Award for Research Excellence. I am a social computing researcher. My research interests lie at the intersection of human-computer interaction, machine learning, and social psychology. I have broad interests in the design and social impact of AI technologies in online and offline communities. JOSEPH A. KONSTAN University of Minnesota - Twin Cities konstan@umn.edu Joseph A. Konstan is Distinguished McKnight Professor and Distinguished University Teaching Professor in the Department of Computer Science and Engineering at the University of Minnesota, where he also holds the title Adjunct Professor of Public Health. His research addresses a variety of human-computer interaction issues, including personalization (particularly through recommender systems), eliciting on-line participation, designing computer systems to improve public health, and ethical issues in research online. He is probably best known for his work in collaborative filtering recommenders (the GroupLens project, which recently won the ACM Software Systems Award). New Future of Work 2020, August 3–5, 2020 © 2020 Copyright held by the owner/author(s).